OVERALL MEANING OF QURANIC VERSES: A THEORETICAL STUDY - Alsulami, Abdulaziz Rabeh; Alghamdi, Mohammed Ali (Journal of Islamic Sciences, 2019)
This Study deals with the statement of the overall meaning، the definition of its term، the reasons for its appearance، its origin، its development، and the interpretations it contains. The Study is also concerned with the explanation of the interpreters’ methods of the overall meaning، as well as the importance of knowing the overall meaning of the Qura’nic verses، the foundations and elements of its constructions، and its controls, The main purpose of the Study is to clarify the importance of the overall meaning as a method of interpretation، as well as to clarify the grounds that those who want to interpret the Qur’an in the general sense should be aware of، and to explain some of those grounds in the context of their interpretation. The Study highlights these grounds، and that they are the causes of descent، copying، and the virtues of the Qur’an، the verses shown، and the analogies of the verse، the hadiths shown، the direction of the verse، the controversy in the verse، the public، private، and the spoken، the concept، that is strange in Qur’an، its context، readings، and extrapolation. The Study shows the care of the interpreters in the general sense in their interpretations، and that it is not mentioned in their interpretations in vain، it is done for certain purposes، and is based on strong and robust foundations، and that the approach of our predecessors، may God be pleased with them. The Study concludes that the significance of the overall meaning is important، and that it is considered to be a distinct type among the other interpretations. It is the origin and the basis، and the more the interpreter is knowledgeable and insight، the more overall the meaning is. The Study recommends the inclusion of a training subject in the methodological year of the Masters program، in which the student will formulate the overall meaning of some verses of the Holy Qura’n، and intensify the study of the overall meaning of Imam Ibn Jarir al- Tabari.